RANCANG BANGUN SISTEM INFORMASI LOWONGAN KERJA BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Handini Widyastuti; Insan Muhammad Muttaqien (Universitas Sahid Surakarta, 2019)
Information exchange becomes one of the most important needs in life today. Included is the need for information on job vacancies. Therefore, jobseekers need a job search application based on specified criteria, as well as employers get the appropriate worker candidate with the required qualifications. The method used in making this webbased information system is waterfall method. In its implementation using HTML, CSS, and PHP Codeigniter framework as data processing framework with MySQL database. The result of this programming is a website job vacancy information that facilitate jobseeker in search (based on the criteria of interest) and apply online application. Employers may publish vacancies as well as obtain candidates that meet the required qualifications. Employer can create an interview agenda with the applicant (jobseeker). The use of PHP codeigniter framework that apply the concept of OOP and MVC makes the structure of the code becomes more structured to facilitate the maintenance and development